Physics-based algorithm to simulate tree dynamics under wind load - Xu, Lifeng; Yang, Zhongzhu; Ding, Weilong; Buck-Sorlin, Gerhard (International journal of agricultural and biological engineering, 2020)
Rapid development in the different computer science fields during the recent decades has facilitated the creation of new applications in the area of dynamic simulation of plant development. Among these new applications, simulation of trees swaying in the wind is of great importance, as those computer graphics related areas, e.g., computer games, tree cultivation and forest management simulations, help a lot in revealing the mechanisms of tree dynamics under wind load. However, it is a big challenge to balance the effect of visualization in real time and calculation efficiency for any simulation algorithm. A physics-based algorithm to simulate tree dynamics under wind load was proposed in this study. A mechanistic model simulating the bending of a cantilever beam was used within the algorithm to simulate deformation of stems, and the algorithm was integrated with a landscape model in which different types of trees were constructed with an L-system-based formalism. Simulation results show that realistic dynamic effects can be achieved with reasonably high computational efficiency.